THE INFLUENCE OF FIRM SIZE, DEBT POLICY, FINANCIAL PERFORMANCE, AND CAPITAL STRUCTURE ON STOCK RETURNS IN MINING COMPANIES LISTED ON THE IDX IN 2018–2024 - Aprianingsih, Heny; darmanto; Budi Utami, Wikan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to determine the partial influence of firm size, debt policy, financial performance, and capital structure on stock returns in mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2024. The sample consisted of 15 mining companies listed on the IDX during that period. The results indicate that firm size does not significantly affect stock returns, suggesting that company size is not a primary consideration for investors when assessing stock return prospects in the mining sector. Debt policy also does not have a significant effect, indicating that a company's leverage level is not a key factor in investment decisions in this sector. Financial performance similarly does not significantly influence stock returns, suggesting that historical financial ratios are less relevant for predicting stock price movements in mining. However, capital structure has a significant positive effect on stock returns, indicating that a company's capital composition is an important factor for investors. An optimal capital structure can signal the company's ability to manage risks and seize growth opportunities. Simultaneously, all independent variables together significantly influence stock returns, highlighting that internal company factors collectively have limited impact, as investors tend to focus on external factors such as commodity prices, global economic conditions, and regulations. Keywords: Firm Size, Debt Policy, Financial Performance, Capital Structure, Stock Return